2018
DOI: 10.1002/jctb.5811
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic analysis (TEA) of microbial oil production from waste resources as part of a biorefinery concept: assessment at multiple scales under uncertainty

Abstract: BACKGROUND: Microbial oils -often termed single cell oils (SCOs) -offer an alternative to terrestrial oil crops across the energy, food and chemical industries. In addition to oils, a range of secondary metabolites can be produced from the heterotrophic organisms as part of a biorefinery system. Techno-economic analysis (TEA) is an important tool for evaluating economic viability, and although TEA is subject to high uncertainties where production is still at the laboratory scale, the tool can play a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 41 publications
1
66
2
1
Order By: Relevance
“…) is contrary to what has been observed with native M. pulcherrima , where lipid accumulation was enhanced at lower cultivation temperatures . Potential reasons for this are that the strain used in this study was evolved at 25 °C, but also that the fermentation took place under controlled oxygen (DO 50%) and pH (pH 4) rather than in shake flasks with limited process parameter control. In this respect, it has been shown that native M. pulcherrima achieves far higher lipid contents in STRs, presumably due to the higher oxygen availability, which is not the case with the evolved strain .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…) is contrary to what has been observed with native M. pulcherrima , where lipid accumulation was enhanced at lower cultivation temperatures . Potential reasons for this are that the strain used in this study was evolved at 25 °C, but also that the fermentation took place under controlled oxygen (DO 50%) and pH (pH 4) rather than in shake flasks with limited process parameter control. In this respect, it has been shown that native M. pulcherrima achieves far higher lipid contents in STRs, presumably due to the higher oxygen availability, which is not the case with the evolved strain .…”
Section: Discussioncontrasting
confidence: 68%
“…Research has driven the technology forward in the last century, but compelling data on the effect of basic process parameters such as temperature, pH and nutrition on yeast lipid production, foremost its kinetics, is, especially in relation to the wide range of oleaginous yeasts, 2 remarkably rare. Enhanced lipid production kinetics are a crucial factor for commercial deployment of yeast lipid technology, 3,4 and it is surprising that acquisition of corresponding data is often omitted in process development. 5 Among the known oleaginous yeasts, the majority are cultured around 30°C with the higher temperatures generally leading to advanced reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the growing demand for terrestrial oils, oleaginous microorganisms offer a promising alternative. These microbes are generally defined as producing over 20% (w/w) lipids (Thorpe & Ratledge, ), though the cost associated with the bulk production of those single cell oils are still too high for commercial viability (Koutinas, Chatzifragkou, Kopsahelis, Papanikolaou, & Kookos, ; Parsons, Abeln, McManus, & Chuck, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the key issue with M. pulcherrima is its relatively slow growth cycle (Abeln et al, ; Chantasuban et al, ; Li, Zhao, & Bai, ; Pan, Kwak, & Rhee, ; Santomauro et al, ; Zhang et al, ; Zhao, Hu, Wu, Shen, & Zhao, ): partly contingent upon a relatively low cultivation temperature promoting lipid synthesis (Santomauro et al, ), lipid productivities of up to only 0.05 g L −1 h −1 are reported in batch fermentation (Abeln et al, ). To yet facilitate economically feasible cultivation, the space‐time yield requires improvement (Koutinas et al, ; Parsons et al, ). One promising approach could be the cultivation at high cell densities, which is proposed to facilitate higher rates of reaction, assuredly reduces reactor volume, and facilitates downstream processing (Bunch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional oil crops are still the main source for renewable oil, microbes gain in importance, as they have shorter life cycle, do not dependent on arable land and do not necessarily compete with human or animal food production. Nonetheless, the high processing costs constitute a major barrier for an economically viable large-scale production of microbial oil (Braunwald et al 2014;Parsons et al 2018) .…”
Section: Introductionmentioning
confidence: 99%